Lilliputian hardware platform for scientific applications - Iyer, Neelima; Khatavkar, Rupali; Joshi, Bhagyashree; Upadhye, V. (International Journal of Software Engineering and Knowledge Engineering, 2005)
Microcontroller plays an important role in gearing up scientific applications for measurements, data acquisition and controls. With the advent of technology in microcontrollers, a new era in the form of microconverter is available at the user's doorstep. Benefited by the excellent features of Analog Devices' microconverter chip ADuC 842, an attempt has been made to develop a Lilliputian platform for scientific applications at National Chemical Laboratory (NCL), Pune. A real time system has been developed for measuring surface tension exerted by Langmuir films formed at air water interface. The films are compressed by smooth and precision barrier mechanism through DC motor in a controlled manner. (IC)-C-2 compatible EEPROM is provided on board for data storage and it can be communicated to a PC through RS232 link for further analysis. The other features provided are, In-circuit programming for firmware updating, keyboard functioning for special routine executions, (IC)-C-2 compatible RTC and battery backup. The software has been completely developed using assembly language programming. Intelligent Lilliputian platform designed using ADuC 842 chip and graphic LCD for real time plotting of surface pressure area isotherm of Langmuir films has been developed and tested successfully at NCL.
Keywords: Langmuir films; microconverter

Assembly of phase transferred nickel nanoparticles at air-water interface using Langmuir-Blodgett technique - Bala, Tanushree; Joshi, Bhagyashree; Iyer, Neelima; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2006)
Development of simple and efficient protocol for the synthesis of Ni nanoparticles in aqueous media and their subsequent phase transfer to organic media is reported. The synthesis of nickel nanoparticles in aqueous medium is accomplished by reducing the nickel nitrate with sodium borohydricle in presence of oleic acid. It results in the formation of nickel nanoparticles capped with oleic acid. The pristine oleic acid capped nickel nanoparticles were then phase transferred to nonpolar solvents such as toluene using stearic acid. The phase transfer was effective probably due to the space exchange between the oleic acid moiety and stearic acid molecules. The hydrophobized Ni thus obtained was organized at the air-water interface and it was observed that by controlling the pressure and concentration of hydrophobized Ni nanoparticles at air-water interface, linear ribbon like assemblies could be obtained. The organization process was followed by surface pressure-area isotherm measurement and Brewster Angle Microscopy.
Keywords: assembly; Langmuir-Blodgett technique; Ni nanoparticles; Phase transfer

Brewster angle microscope - an excellent tool for nanoscience researchers - Joshi, Bhagyashree; Khatavkar, Rupali; Iyer, Neelima (Synthesis and Reactivity in Inorganic Metal - Organic and Nano-Metal Chemistry, 2006)

Microconverter ADuC842 and LabVIEW platform ? a best suitable approach for real time plotting of pressure area isotherm of a monolayer - Iyer, Neelima; Khatavkar, Rupali; Joshi, Bhagyashree (Proceedings of the 5th WSEAS Int. Conf. on Electronics, Hardware, Wireless and Optical Communications, 2006)